IFOMA after Migration Posttraumatic Impact Scale Development, Validity and Reliability Study - Ilknur Aydin Avci; Figen Cavusoglu; Ozge Oz Yildirim; Mehmet Korkmaz and Ayse Cal (Professor Despina Sapountzi-Krepia, 2024)
IFOMA after Migration Posttraumatic Impact Scale Development, Validity and Reliability Study